A metabolic sensor in action: News from the ATP-sensitive K+-channel - Trapp, S; Ashcroft, F (1997)
The KATP channel provides a link between metabolism and electrical activity in numerous cell types. It can be reconstituted by coexpression of two subunits, a pore-forming inward rectifier K+ channel and a regulatory subunit, the sulfonylurea receptor. Site-directed mutagenesis of these subunits enables analysis of the complex regulation of KATP, channel activity by metabolism and therapeutic drugs.